Treatment of class III malocclusion in primary and mixed dentition with rapid palatal expansion and facemask - Carlos Soldevilla, Luciano (2011)
We report the follow-up of a cross-bite clinical case which initially undertook the use of a Rigid acrylic-bonded palatal appliance that after stabilization treatment and coincident with the anterior tooth replacement, suffered a recurrence of anterior crossbite wich was corrected with the use of facemask. The purpose of correcting the crossbite at early ages allowed to drive improvements in the Class III skeletal pattern and reduces the amount of compensation to dental and skeletal discrepancies are usually associated with severe skeletal malocclusion in adolescence, however, the disadvantage is that the prolonged time treatment and the potential instability of the changes obtained. Independently the determinant of recurrence, is recommended the overcorrection overjet and molar relationship as a tool for long term stability.